ASOSIASI MEREK DAN PENGARUHNYA TERHADAP RESPON KONSUMEN PADA PENGGUNA SEPATU MEREK ADIDAS DI SURABAYA - Donny Prasetya (STIE Perbanas Surabaya, 2012)
So far, brand or trademark has become the crucial factor in any business. There fore, a good brand may provide some beneficial for the consumers. This research aims to find out why ADIDAS, at the moment, is considered the second place under the NIKE and as well as why the users are persistently to use ADIDAS shoes although many competitors are viewed through a variable association of brand extension of the brand recommendation and price premium. This study employs SEM with the help of AMOS analysis tool. Questioniaires were distributed to the consumers of ADIDAS shoes in Surabaya, and a scale Likert with scale of 1 to 5 was also done for analysis. The study shows that the influence that was not significant between the brand associations and the extension of the brand. Another finding is that there is significant effect between brand association and recommendations and the last of the influence of being not significant between association brands and price premium. To advance we suggested that the company of ADIDAS is more intensively to conduct a longer promotion for the products with the brand of its shoes such as: a jacket, a bag, t-shirt and others and make improvement quality and innovation on these products other than shoes. Second, ADIDAS Company should adjust to the prices in each of their products espsecially in shoes product. This is due to the condition that the users think that ADIDAS shoes price for the company is set very expensive.